Structural analysis of the ribosome-associated complex (RAC) reveals an unusual Hsp70/Hsp40 interaction - Fiaux Vogel, Jocelyne; Horst, Janina; Scior, Annika; Preißler, Steffen; Koplin, Ansgar; Bukau, Bernd; Deuerling, Elke (The journal of biological chemistry, 2010)
Yeast Zuotin and Ssz are members of the conserved Hsp40 and Hsp70 chaperone families, respectively, but compared with canonical homologs, they atypically form a stable heterodimer termed ribosome-associated complex (RAC). RAC acts as co-chaperone for another Hsp70 to assist de novo protein folding. In this study, we identified the molecular basis for the unusual Hsp70/Hsp40 pairing using amide hydrogen exchange (HX) coupled with mass spectrometry and mutational analysis. Association of Ssz with Zuotin strongly decreased the conformational dynamics mainly in the C-terminal domain of Ssz, whereas Zuotin acquired strong conformational stabilization in its N-terminal segment. Deletion of the highly flexible N terminus of Zuotin abolished stable association with Ssz in vitro and caused a phenotype resembling the loss of Ssz function in vivo. Thus, the C-terminal domain of Ssz, the N-terminal extension of Zuotin, and their mutual stabilization are the major structural determinants for RAC assembly. We furthermore found dynamic changes in the J-domain of Zuotin upon complex formation that might be crucial for RAC co-chaperone function. Taken together, we present a novel mechanism for converting Zuotin and Ssz chaperones into a functionally active dimer.